Lithium battery high-temperature-resistant flame-retardant composite diaphragm and preparation method thereof
By coating the flame retardant layer of modified phenolic resin and natural clay mineral nanotubes on the lithium-ion battery polyolefin separator, the problems of poor affinity of the separator for electrolytes, unstable thermal dimensions and flammability are solved, and higher thermal safety and electrolyte liquid absorption are achieved.
Patent Information
- Application Number
- CN202411488612.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The existing lithium-ion battery polyolefin separators have poor affinity for electrolytes, unstable thermal dimensions and are flammable, making it difficult to meet the needs of high energy density and high power output.
A lithium battery high-temperature flame retardant composite separator is used, which consists of a polyolefin separator and a flame retardant layer composed of a modified phenolic resin sub-micron particles, natural clay mineral nanotubes and additives. The flame retardant layer is applied to the substrate separator by coating method.
The thermal shrinkage rate of the polyolefin separator is significantly reduced, the flame retardant performance is imparted, the thermal safety of the battery cell is improved, the wetting properties of the electrolyte and the liquid absorption rate of the electrolyte are improved.
Smart Images

Figure CN119627363A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a high temperature resistant and flame retardant composite diaphragm for lithium batteries and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used because of their high energy density and long cycle life. The diaphragm is one of the core materials of lithium-ion batteries. Its main function is to separate the positive and negative electrodes of the battery, ensuring the passage of lithium ions. It is a thin film with a microporous structure. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and affects the capacity and cycle of the battery.
[0003] At present, polyolefin separators such as polypropylene separator (PP) and polyethylene separator (PE) are mainly used commercially. However, due to their thermal dimensional instability, flammability and poor affinity for electrolyte, they are difficult to meet the needs of high energy density and high power output. The future development direction of lithium batteries is to improve safety and energy density. The current mainstream solution is to coat the separator, among which ceramic material coating is the most widely used. However, the ceramic coating is relatively dense and has a low liquid absorption rate, which is not conducive to the improvement of the energy density of the battery cell. In addition, the improvement of flame retardant properties of ceramic-modified polyolefin separators is limited. Summary of the invention
[0004] The purpose of the present invention is to solve the shortcomings of the prior art lithium-ion battery polyolefin separator, such as poor affinity for electrolyte, thermal dimensional instability and flammability, and to propose a high-temperature resistant and flame-retardant composite separator for lithium batteries.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A high temperature resistant and flame retardant composite diaphragm for lithium battery, which is composed of a base diaphragm and a flame retardant layer on its outer side, wherein the base diaphragm is a polyolefin diaphragm, and the flame retardant layer is made of modified phenolic resin submicron particles, natural clay mineral nanotubes and additives;
[0007] The mass ratio of the modified phenolic resin submicron particles to the natural clay mineral nanotubes is 30% to 95%: 5% to 70%.
[0008] Preferably, the modified phenolic resin is at least one of boron-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin, titanium-modified phenolic resin, molybdenum-modified phenolic resin and zirconium-modified phenolic resin;
[0009] The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.
[0010] Preferably, the thickness of the substrate diaphragm is 5 to 35 μm;
[0011] The equivalent particle size d(0.5) of the modified phenolic submicron particles is 0.05 μm to 5 μm;
[0012] The specific surface area of the natural clay mineral nanotubes is 10 to 400 m2 / g.
[0013] Preferably, the auxiliary agent includes a dispersant, a wetting agent and a binder.
[0014] More preferably, the dispersant and wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butylnaphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose;
[0015] The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.
[0016] Preferably, the flame retardant layer density of the composite diaphragm is 0.8-9.8 g / m2, the thermal shrinkage of the composite diaphragm at 200°C for 30 min is ≤5%, the electrolyte absorption rate is 90.6-386.1%, and the ionic conductivity is 0.4-2.8 mS / cm.
[0017] The method for preparing the high temperature resistant and flame retardant composite diaphragm of the lithium battery comprises the following steps:
[0018] S10, mixing the modified phenolic resin particles, the natural clay mineral nanotubes, the dispersant, the wetting agent and water to obtain a mixed solution;
[0019] S20, adding a binder to the uniformly mixed solution to obtain a slurry,
[0020] S30, coating the slurry on the surface of the polyolefin diaphragm and drying to obtain a modified diaphragm.
[0021] Preferably, the step S10 specifically includes:
[0022] S101, mixing the modified phenolic resin submicron particles, natural clay mineral nanotubes and water and performing ultrasonic dispersion treatment for 20 minutes to obtain a first intermediate solution;
[0023] S102, adding a dispersant and a wetting agent into the first intermediate solution and stirring for more than 6 hours to obtain the mixed solution.
[0024] Preferably, the mass percentage concentration of the modified phenolic resin particles is 1 to 60%;
[0025] The mass percentage concentration of the natural clay mineral nanotubes is 1 to 40%;
[0026] The mass percentage concentration of the dispersant is 0.01 to 15%;
[0027] The mass percentage concentration of the wetting agent is 0.01 to 15%;
[0028] The mass ratio of the adhesive to the slurry is 1 to 10%.
[0029] Preferably, the step S30 is specifically as follows:
[0030] The wet composite film is placed at room temperature for drying for 30 minutes, and then transferred to a blast oven for drying to obtain the organic-inorganic composite flame-retardant diaphragm for a lithium battery;
[0031] The drying temperature of the blast oven is set to 80°C, and the drying is carried out in the blast oven for 5 to 15 minutes.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] 1. The composite flame-retardant diaphragm prepared by the present invention can significantly reduce the thermal shrinkage of the polyolefin diaphragm, impart flame retardancy to it, comprehensively enhance the thermal safety of the battery monomer, improve the wettability to the electrolyte, and increase the liquid absorption rate;
[0034] 2. The modified phenolic resin used in the present invention has elements such as boron, silicon, magnesium, and aluminum participating in the reaction during the high-temperature decomposition process. It not only has a flame retardant function itself, but also can catalyze the organic resin to form a protective layer with a dense structure on the surface of the diaphragm through a synergistic effect, effectively isolating oxygen and inhibiting further combustion of the base film, thereby showing excellent flame retardancy;
[0035] 3. The slurry used in the preparation of the composite flame-retardant diaphragm in the present invention is an environmentally friendly water-based slurry, which is simple to operate and has good compatibility. In addition, the raw materials used are in abundant reserves, and the industrial production conditions are perfect, which is convenient for controlling costs.
[0036] The invention has a novel design, effectively improves the thermal stability and flame retardancy of the polyolefin separator in the lithium battery, comprehensively enhances the thermal safety of the battery monomer, and improves the wettability of the electrolyte and increases the liquid absorption rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The present invention is a flow chart of the preparation method of the high temperature resistant and flame retardant composite diaphragm for lithium batteries.
[0038] Figure 2 This is the SEM image of Celgard's 10um PE separator.
[0039] Figure 3This is a SEM image of the surface of the composite diaphragm prepared in Example 2 of the present invention.
[0040] Figure 4 These are actual photos of the PE diaphragm before and after heating at 200°C and the PE composite flame-retardant diaphragm prepared in Example 1.
[0041] Figure 5 These are photos of the PE diaphragm and the PE composite flame-retardant diaphragm prepared in Example 1 before and after ignition. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0043] Reference Figure 1-5 A high temperature resistant and flame retardant composite diaphragm for lithium battery, comprising a base diaphragm and a flame retardant layer on its outer side, wherein the base diaphragm is a polyolefin diaphragm, and the flame retardant layer is made of modified phenolic resin submicron particles, natural clay mineral nanotubes and additives; wherein the mass ratio of modified phenolic resin submicron particles to natural clay mineral nanotubes is 30% to 95%: 5% to 70%. The flame retardant layer density of the composite diaphragm of the present invention is 0.8 to 9.8 g / m2, the heat shrinkage rate is ≤5% for 30 minutes at 200°C, the electrolyte absorption rate is 90.6 to 386.1%, and the ionic conductivity is 0.4 to 2.8 mS / cm.
[0044] The modified phenolic resin is at least one of boron-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin, titanium-modified phenolic resin, molybdenum-modified phenolic resin, and zirconium-modified phenolic resin; the natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.
[0045] The thickness of the selected substrate polyolefin diaphragm is 5-35 μm; the equivalent particle size d(0.5) of the modified phenolic submicron particles is 0.05 μm-5 μm; and the specific surface area of the natural clay mineral nanotubes is 10-400 m2 / g.
[0046] The auxiliary agent includes a dispersant, a wetting agent and a binder, wherein the dispersant and the wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butylnaphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose; the binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.
[0047] The preparation method of the composite flame-retardant diaphragm of the present invention is as follows: phenolic powder modified by boron / molybdenum / silicon / phosphorus / titanium / zirconium is heated and solidified into resin, the modified phenolic resin is processed into submicron particles by mechanical processing from top to bottom, and the particles are dispersed in an aqueous solution together with natural clay mineral nanotubes, and functional additives such as dispersants, wetting agents and binders are added to prepare a slurry, which is then coated on a polyolefin diaphragm. The high-temperature resistant flame-retardant composite diaphragm for lithium batteries can significantly reduce the thermal shrinkage of the polyolefin diaphragm, impart flame-retardant properties to it, and comprehensively improve the thermal safety of the battery cell; at the same time, the wettability to the electrolyte, the electrolyte absorption rate and the ionic conductivity are improved.
[0048] The following is a specific embodiment according to this preparation method:
[0049] Embodiment 1
[0050] In this embodiment, the modified phenolic resin is boron-modified phenolic resin; the dispersant, wetting agent and adhesive are all purchased from BYK Chemical, the specific brands are as follows: the dispersant is an ammonium acrylate dispersant, BYK-LPC20992; the wetting agent is a silicone surfactant wetting agent, BYK-LPX20990; the adhesive is a polyacrylate adhesive, BYK-LPC22346; the diaphragm substrate is a commercial polyolefin diaphragm, specifically, a 10μm thick PE diaphragm from Celgard.
[0051] Preliminary treatment of raw materials before preparation of high temperature resistant flame retardant composite diaphragm:
[0052] Preparation of boron-modified phenolic resin microparticles:
[0053] The boron-modified phenolic resin solid powder is placed in a muffle furnace and the temperature is increased gradually, first to about 140° C. to melt it into a liquid state, and then to 170° C. and maintained for 2 hours to allow it to fully solidify.
[0054] The solidified boron-modified phenolic resin was taken out, and the solid was appropriately crushed with a pestle, and then put into a universal grinder, the speed was set to 12000 rpm, and the cumulative crushing was 30 minutes to obtain the boron-modified phenolic resin powder.
[0055] Substrate diaphragm treatment:
[0056] The PE diaphragm does not require any special treatment before coating, just ensure that the diaphragm surface is clean.
[0057] The specific preparation method of the high temperature resistant flame retardant composite diaphragm is as follows:
[0058] Step 1: Prepare a modified phenolic resin submicron particle suspension. Mix the boron-modified phenolic resin powder with deionized water, add it to a vertical ball mill at a solid-liquid mass ratio of 1 to 10, control the speed at 120 to 180 rpm, and the time is 96 hours.
[0059] The slurry after ball milling was directly fed into a nano sand mill for the final mechanical processing, with the speed controlled at 1800 rpm for 12 hours to obtain a suspension of submicron particles of modified phenolic resin. The equivalent particle size d(0.5) of the prepared submicron boron-modified phenolic resin was 800 nm.
[0060] Step 2: Prepare a high temperature flame retardant diaphragm coating slurry. Prepare 90 parts by mass of boron modified phenolic resin submicron particle powder and 10 parts by mass of halloysite nanotubes into a suspension with a solid content of 11%. Subsequently, add 2% by mass of naphthalenesulfonic acid formaldehyde condensate and 1% BYK-333 wetting agent, transfer to a magnetic stirrer and stir for 24 hours. After mixing evenly (the mixed solution is left to stand for half an hour without obvious precipitation), add 5% of acrylate adhesive and continue stirring for 6 hours to obtain an aqueous coating slurry blended with boron modified phenolic resin particles and halloysite nanotubes.
[0061] Step three, slurry coating, use an automatic coating machine to evenly coat the above slurry on the PE diaphragm to obtain a composite wet film, place it at room temperature for 30 minutes (taking 25°C room temperature as an example), and after there is no water mark on the surface of the composite diaphragm, transfer it to 80°C blast oven for vacuum drying for 10 minutes to obtain a PE composite diaphragm coated with modified phenolic resin particles and halloysite nanotubes on one side. Use an automatic coating machine to evenly coat the above slurry on the PE diaphragm to obtain a composite wet film, place it at room temperature for 30 minutes (taking 25°C room temperature as an example), and after there is no water mark on the surface of the composite diaphragm, transfer it to 80°C blast oven for vacuum drying for 10 minutes to obtain a PE composite diaphragm coated with modified phenolic resin particles and halloysite nanotubes on one side. Repeat the above steps to obtain a PE composite diaphragm coated with high temperature resistant materials on both sides, and obtain a PE composite diaphragm coated with high temperature resistant materials on both sides (hereinafter referred to as BPF@PE diaphragm).
[0062] Embodiment 2
[0063] The method is basically the same as Example 1, except that, in the preparation step 2, 70 parts by mass of boron-modified phenolic resin submicron particle powder and 30 parts by mass of halloysite nanotubes are selected.
[0064] Embodiment 3
[0065] The same as Example 1, except that in the preparation step 2, 50 parts by mass of boron-modified phenolic resin submicron particle powder and 50 parts by mass of halloysite nanotubes are selected.
[0066] Embodiment 4
[0067] The same as Example 1, except that in the preparation step 2, 30 parts by mass of boron-modified phenolic resin submicron particle powder and 70 parts by mass of halloysite nanotubes are selected.
[0068] Comparative Example
[0069] Without the above treatment, unmodified clean PE diaphragm is selected.
[0070] Evaluation Method
[0071] The BPF@PE diaphragm prepared above was subjected to performance tests, including air permeability, weight, thickness, surface density, liquid absorption, micromorphology, ionic conductivity, thermal dimensional stability and flame retardancy.
[0072] The specific performance test methods are as follows:
[0073] 1. Air permeability test: Use the American Gurley 4110N air permeability tester to test the air permeability of the diaphragm. The air permeability of the diaphragm reflects the tortuosity of the internal pores of the diaphragm and the true path of ion diffusion. It is proportional to the ion conductivity and can be evaluated by the Gurley value. The Gurley value refers to the time required for a certain amount of air to pass through a unit area of the diaphragm under a certain specified pressure, in seconds.
[0074] 2. Surface density test: The surface density of the BPF@PE diaphragm is calculated by slicing and weighing. The diaphragm is cut into discs with a diameter of 16.5 mm using a cutting machine. The discs are weighed one by one and the average value is calculated.
[0075] 3. Thickness test: Use a handheld thickness gauge to test the thickness of the BPF@PE diaphragm.
[0076] 4. Liquid absorption rate test: Use the weighing method to test the liquid absorption rate of the diaphragm, that is, calculate the liquid absorption rate of the diaphragm by the change in weight before and after the diaphragm absorbs liquid: weigh a disc membrane with a diameter of 16.5 mm, and then immerse it in a liquid electrolyte of EC:DMC (3:7, v / v, containing 1.0 mol / L LiPF6) for 1 hour. After taking it out, gently wipe off the surface liquid with filter paper, weigh it, and calculate the liquid absorption rate EU. The calculation formula is:
[0077] EU(%)=(W2-W1) / W1×100%
[0078] Among them, W1 and W2 are the mass (g) of the diaphragm before and after wetting in the electrolyte.
[0079] 5. Detection of diaphragm surface morphology: Use a cold field scanning electron microscope to observe the surface morphology of the flame retardant diaphragm.
[0080] 6. Ionic conductivity test: The bulk impedance of the BPF@PE diaphragm was tested on an electrochemical workstation (Bio-Logic VSP-300) by electrochemical impedance spectroscopy (EIS), and its ionic conductivity was obtained. A stainless steel symmetrical cell was assembled for testing. The frequency range was 106 to 10-1 Hz, and the AC amplitude was 10 mV. The ionic conductivity calculation formula is as follows:
[0081] σ=D / RS
[0082] Wherein, σ represents the ionic conductivity of the membrane; D represents the thickness of the membrane; R is the horizontal intercept of the Nyquist plot; and S represents the area of the membrane.
[0083] 7. Thermal dimensional stability test: Observe the dimensional changes of the BPF@PE diaphragm before and after heating at 200°C for 30 minutes.
[0084] 8. Flame retardant performance test: Use a cutting machine to cut the diaphragm into discs with a diameter of 16.5 mm. Burn the BPF@PE diaphragm on the flame of an alcohol lamp. After staining, remove the flame range and record the burning phenomenon with a digital camera.
[0085] The above test results are statistically analyzed and recorded in Table 1.
[0086] Table 1. Composite flame retardant diaphragm performance test data
[0087]
[0088]
[0089] Combined with the data in Table 1, the present invention uses a polyolefin separator as a substrate, and uses a coating method to coat the organic modified phenolic resin particles and inorganic natural clay mineral nanotubes on the surface of the polyolefin separator. The resulting BPF@PE separator has the advantages of high temperature resistance, flame retardancy, and high electrolyte absorption rate. It also improves the wettability of the separator to the electrolyte, and increases the electrolyte absorption rate and ionic conductivity.
[0090] pass Figure 2 and Figure 3 Observation of the SEM image of the diaphragm surface, Figure 2 The surface of the commercial PE separator shows a large number of evenly distributed pores; Figure 3 In the BPF@PE separator prepared by the scheme in Example 1, the boron-modified phenolic resin particles and the one-dimensional nanotubes uniformly cover the base film, indicating that the slurry formula has good coating properties for polyolefin separators. In addition, there are a large number of pores between the boron-modified phenolic resin particles and the nanotubes, which absorb electrolytes and provide abundant channels for the transmission of lithium ions.
[0091] Combination Figure 4 From the comparison of the heating experiments at 200°C on the diaphragms, it can be seen that the commercial PE diaphragm obviously shrinks, melts and then solidifies, changing from a round shape to a tiny light white plastic mass, while the BPF@PE diaphragm prepared in Example 1 shows basically no obvious shrinkage after heating. It can be seen that the high temperature resistant flame retardant composite diaphragm prepared in this application has very excellent thermal dimensional stability.
[0092] Combined with Table 1 Figure 5 From the comparison of the burning experiments on the diaphragms, it can be seen that the PE diaphragm shrinks rapidly into a ball the moment it contacts the flame, and then burns out; while the BPF@PE diaphragm does not shrink significantly when it contacts the flame, and can maintain its basic shape. After leaving the flame, the burning part begins to carbonize, and then the burning flame becomes smaller until it goes out. This is due to the participation of the boron element in the high-temperature decomposition process of the boron phenolic resin. The natural mineral nanomaterials contain inorganic elements such as silicon, magnesium, and aluminum, which not only have flame retardant functions themselves, but can also catalyze organic resins. Through synergistic effects, a protective layer with a dense structure is formed on the surface of the diaphragm, which effectively isolates oxygen and inhibits further combustion of the base film, thereby showing excellent flame retardancy.
[0093] Obviously, the high temperature resistant and flame retardant composite diaphragm in the present application has excellent properties of high temperature resistance, flame retardancy, and high electrolyte absorption rate, and its use in batteries can greatly improve the thermal safety of battery cells.
[0094] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A high temperature resistant and flame retardant composite diaphragm for lithium battery, characterized in that: It consists of a base membrane and a flame retardant layer on its outer side, wherein the base membrane is a polyolefin membrane, and the flame retardant layer is made of modified phenolic resin submicron particles, natural clay mineral nanotubes and additives; The mass ratio of the modified phenolic resin submicron particles to the natural clay mineral nanotubes is 30% to 95%: 5% to 70%.
2. A high temperature resistant and flame retardant composite diaphragm for lithium battery according to claim 1, characterized in that: The modified phenolic resin is at least one of boron-modified phenolic resin, phosphorus-modified phenolic resin, silicon-modified phenolic resin, titanium-modified phenolic resin, molybdenum-modified phenolic resin and zirconium-modified phenolic resin; The natural clay mineral nanotube is at least one of attapulgite nanotube and halloysite nanotube.
3. The high temperature resistant and flame retardant composite diaphragm for lithium battery according to claim 1, characterized in that: The thickness of the substrate diaphragm is 5 to 35 μm; The equivalent particle size d(0.5) of the modified phenolic submicron particles is 0.05 μm to 5 μm; The specific surface area of the natural clay mineral nanotubes is 10 to 400 m2 / g.
4. The high temperature resistant and flame retardant composite diaphragm for lithium battery according to claim 1, characterized in that: The auxiliary agents include dispersants, wetting agents and binders.
5. A high temperature resistant and flame retardant composite diaphragm for lithium battery according to claim 4, characterized in that: The dispersant and wetting agent are at least one of fluoroalkyl methoxy alcohol ether, polyoxyethylene alkylamine, sodium methylene bisnaphthalene sulfonate, polyether modified silicone, sodium aryl naphthalene sulfonate, sodium dodecylbenzene sulfonate, sodium dodecyl sulfate, sodium perfluorooctanoate, nonylphenol polyoxyethylene ether, sodium butyl naphthalene sulfonate, polyacrylate, polyethylene glycol, and sodium carboxymethyl cellulose; The binder is at least one of styrene-butadiene rubber, sodium carboxymethyl cellulose, lithium polyacrylate, and polyacrylonitrile multipolymer.
6. A high temperature resistant and flame retardant composite diaphragm for lithium battery according to any one of claims 1 to 5, characterized in that: The flame retardant layer density of the composite diaphragm is 0.8-9.8 g / m2, the thermal shrinkage rate of the composite diaphragm at 200°C for 30 minutes is ≤5%, the electrolyte absorption rate is 90.6-386.1%, and the ion conductivity is 0.4-2.8 mS / cm.
7. A method for preparing a high temperature resistant and flame retardant composite diaphragm for a lithium battery according to any one of claims 1 to 6, characterized in that: The following steps are involved: S10, mixing the modified phenolic resin particles, the natural clay mineral nanotubes, the dispersant, the wetting agent and water to obtain a mixed solution; S20, adding a binder to the uniformly mixed solution to obtain a slurry; S30, coating the slurry on the surface of the polyolefin diaphragm and drying to obtain a modified diaphragm.
8. A method for preparing a high temperature resistant and flame retardant composite diaphragm for a lithium battery as claimed in claim 7, characterized in that: The step S10 specifically includes: S101, mixing the modified phenolic resin submicron particles, natural clay mineral nanotubes and water and performing ultrasonic dispersion treatment for 20 minutes to obtain a first intermediate solution; S102, adding a dispersant and a wetting agent into the first intermediate solution and stirring for more than 6 hours to obtain the mixed solution.
9. A method for preparing a high temperature resistant and flame retardant composite diaphragm for a lithium battery as claimed in claim 8, characterized in that: The mass percentage concentration of the modified phenolic resin particles is 1 to 60%; The mass percentage concentration of the natural clay mineral nanotubes is 1 to 40%; The mass percentage concentration of the dispersant is 0.01 to 15%; The mass percentage concentration of the wetting agent is 0.01 to 15%; The mass ratio of the adhesive to the slurry is 1 to 10%.
10. A method for preparing a high temperature resistant and flame retardant composite diaphragm for a lithium battery as claimed in claim 7, characterized in that: The S30 step is specifically as follows: The wet composite film is placed at room temperature for drying for 30 minutes, and then transferred to a blast oven for drying to obtain the organic-inorganic composite flame-retardant separator for lithium batteries; The drying temperature of the blast oven is set to 80° C., and the blast oven is dried for 5 to 15 minutes.
Citation Information
Patent Citations
Polypropylene battery diaphragm containing composite coating and preparation method of polypropylene battery diaphragm
CN105098120A
Coated diaphragm with high temperature resistance and puncture resistance and preparation method thereof
CN116247371A
Battery diaphragm as well as preparation method and application thereof
CN118099660A
Separator for electrochemical device
US20160204406A1